Do Higher Corporate Taxes Reduce Wages? Micro Evidence from Germany - Clemens Fuest; Andreas Peichl; Sebastian Siegloch (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
This paper estimates the incidence of corporate taxes on wages using a 20-year panel of German municipalities exploiting 6,800 tax changes for identication. Using event study designs and differences-in-differences models, we find that workers bear about half of the total tax burden. Administrative linked employer-employee data allow us to estimate heterogeneous firm and worker effects. Our findings highlight the importace of labor market institutions and profit-shifting opportunities for the incidence of corporate taxes on wages. Moreover, we show that low-skilled, young and female employees bear a larger share of the tax burden. This has important distributive implications.
Keywords: H20; H70; J30; 330; business taxation; incidence; administrative data; local taxation